2020
DOI: 10.1021/acssensors.0c02413
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Generation of Thiyl Radicals: A General Method of Rapidly Connecting Molecules to a Range of Electrodes for Electrochemical and Molecular Electronics Applications

Abstract: Herein, we report ultrasonic generation of thiyl radicals as a general method for functionalizing a range of surfaces with organic molecules. The method is simple, rapid, can be utilized at ambient conditions and involves sonicating a solution of disulfide molecules, homolytically cleaving S–S bonds and generating thiyl radicals that react with the surfaces by forming covalently bound monolayers. Full molecular coverages on conducting oxides (ITO), semiconductors (Si–H), and carbon (GC) electrode surfaces can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 65 publications
(117 reference statements)
0
13
1
Order By: Relevance
“…Current–potential characteristics acquired by cAFM reveals that surface conductivity decreases in the order Si(211) ≫ Si(110) > Si(111). Unlike systems where differences in electrical conductivity are imparted by changes to the chemical nature of the monolayer anchoring group and unlike the inverse relationship between electron-transfer rate constants and the length of alkyl spacers separating the electrode and redox unit, , we found that identical surface chemistry on Si(211), Si(110), and Si(111) leads to comparable kinetics of a redox reaction occurring at the monolayer distal end. While other higher-index substrates, such as Si(311) and Si(411), remain to be investigated, the current findings demonstrate a pronounced facet-dependent electrical conductivity, expand the range of silicon orientations viable as electrode materials, and suggest literature discrepancies in electrochemical rate constants not to be linked to substrate defects, such as ubiquitous surface miscuts.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Current–potential characteristics acquired by cAFM reveals that surface conductivity decreases in the order Si(211) ≫ Si(110) > Si(111). Unlike systems where differences in electrical conductivity are imparted by changes to the chemical nature of the monolayer anchoring group and unlike the inverse relationship between electron-transfer rate constants and the length of alkyl spacers separating the electrode and redox unit, , we found that identical surface chemistry on Si(211), Si(110), and Si(111) leads to comparable kinetics of a redox reaction occurring at the monolayer distal end. While other higher-index substrates, such as Si(311) and Si(411), remain to be investigated, the current findings demonstrate a pronounced facet-dependent electrical conductivity, expand the range of silicon orientations viable as electrode materials, and suggest literature discrepancies in electrochemical rate constants not to be linked to substrate defects, such as ubiquitous surface miscuts.…”
Section: Discussioncontrasting
confidence: 55%
“…First, it is now generally agreed that common mathematical models used in the kinetic analysis of electrochemical data fall short of capturing all the important descriptors of an electrified interface. Second, minor changes to the surface coverage of the redox molecule, monolayer order, and intermolecular interactions , are known to have dramatic kinetic effects. ,, It remains less clear to what extent the chemical nature of the interfacial bondbetween the organic monolayer and electrodeaffects the rates of surface-confined electrochemical reactions. , An important step in the direction of clarifying this overlooked factor was recently published. Dief and Darwish reported that for monolayers grafted on either indium–tin oxide or silicon or carbon electrodes, there is a link between changes in molecular conductivitiesascribed unambiguously to different interfacial bondsand differences in electrochemical rates …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shadows the semiconducting properties of Si and becomes more critical for nanoscale devices whose output will be dominated by the SiO x layer . Conventionally, self-assembled monolayers comprising alkyl chains are used to protect Si from oxidation by blocking oxygen and water from reaching the bulk silicon. , This however comes with an expense of the need for complicated fabrication procedures that often require external effects, such as heat, light, or radical initiators, to enable the formation of covalent bonds between the monolayer-forming molecules and the surface. In addition, the length of the alkyl chain on the molecules in the monolayer should be long enough to enable efficient packing . However, longer-chain molecules also come with the expense of blocking electron transfer. Packing defects in monolayers, which allows for oxygen and water to reach the Si surface, lead to monolayer degradation over time. ,, Hence, there is a need to find a procedure to protect Si from oxidation while preserving the electron-transferring capability of the protecting layer.…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental and applied research on the self-assembly of organic molecules on electrode surfaces continues to be an area of intense research. To date, the focus has been on the formation of self-assembled monolayers (SAMs) on gold electrodes using thiol or disulfide-terminated molecules, but there is increasing interest of forming monolayers on a range of other electrodes. The study by Chidsey and co-workers on Si–C-bound monolayers has helped to expand this research from metals to semiconductors. In particular, monolayers on oxide-free silicon (Si–H) have gained significant interest because they enable combining the traditional semiconducting properties of Si with those of functional organic molecules. , For example, Si-based SAMs have been exploited in solar cell research, biosensors, fundamental electron transfer studies, and molecular electronics. …”
Section: Introductionmentioning
confidence: 99%